Effect of Microwave Exposure and Cooling Time on Physicochemical Characteristics of Modified Sorghum Starch (Sorghum bicolor L. Moench) - Putri, Ajeng Ananda; Anggreini, Riski Ayu; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Sorghum (Sorghum bicolor L. Moench) is a cereal with high starch content. However, natural (native) starch still has many weaknesses in its characteristics. One way to improve it is to modify the starch to have good characteristics and increase its functional value. Physical modification of starch is often used to enhance the properties of natural (native) starch. The starch modification technique with microwave heating and cooling is one of the physical methods that can improve starch characteristics. This study aimed to determine the effect of microwave exposure time and cooling time on the physicochemical characteristics of modified white sorghum starch. This research used a completely randomized design (CRD) with 2 factors and 3 replications. The first treatment is microwave exposure time (2 minutes, 3 minutes, 4 minutes), and the second is cooling time (12 hours, 24 hours, 36 hours). Treatments with significant effect were further tested with the DMRT (Duncan's Multiple Range Test) 5%. The results showed that the best treatment in the sample was modified sorghum starch treated with microwave exposure time of 4 minutes and cooling time of 12 hours which had physicochemical characteristics of moisture content of 8.27%, ash content of 0.78%, starch content of 69.13%, amylose 32.41%, amylopectin of 36.70%, viscosity of 4.97 mPas, swelling power of 27.59 g/g, solubility of 10.68%. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action